Furosemide and spironolactone doses and hyponatremia in patients with heart failure - Ivan Velat; Željko Bušić; Marina Jurić Paić; Viktor Čulić (BMC Pharmacology and Toxicology, 2020)
Abstract Background Hyponatremia, a marker of disease severity and prognosis, has been associated with various clinical factors and drug use, especially diuretics. Methods This observational prospective cohort study enrolled patients hospitalized at the University Hospital Center Split because of heart failure (HF). We investigated the association of clinical variables and cardiovascular drugs, including furosemide, hydrochlorothiazide, spironolactone, and their doses, with the presence of hyponatremia at admission. Results Of the 565 included patients, 32.4% were hyponatremic, 62.6% were males, and the mean age was 73.1 ± 10.6 years. In the univariate analysis, hyponatremic patients were more often current smokers (p = 0.01), alcohol consumers (p = 0.01), receiving spironolactone (p = 0.004) or combination of furosemide and spironolactone (p = 0.003). Patients who received 50 and 100 mg of spironolactone, compared to those receiving 25 mg (p < 0.0001), as well as patients who received 250 to 500 mg of furosemide compared to ≤240 mg (p = 0.001), were significantly more often hyponatremic. In the multivariate analysis, when diuretic doses were accounted for, furosemide doses of 250 to 500 mg (p = 0.009), spironolactone doses of 50 to 100 mg (p = 0.0003), increasing age (p = 0.03), diabetes mellitus (p = 0.02) and alcohol consumption (p = 0.04) were independently associated with hyponatremia. Conclusion High doses of furosemide and spironolactone, or concomitant use of these diuretics, seem to be an important cause of hyponatremia in HF patients, particularly in combination with advanced age, diabetes and alcohol consumption. Diuretic dose reduction may help avoid hyponatremia and improve clinical status and prognosis in such patients.